2000
DOI: 10.1111/j.1471-6402.2000.tb01024.x
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Stereotyping of Emotions

Abstract: Three studies documented the gender stereotypes of emotions and the relationship between gender stereotypes and the interpretation of emotionally expressive behavior. Participants believed women experienced and expressed the majority of the 19 emotions studied (e.g., sadness, fear, sympathy) more often than men. Exceptions included anger and pride, which were thought to be experienced and expressed more often by men. In Study 2, participants interpreted photographs of adults’ambiguous anger/sadness facial expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
318
2
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 439 publications
(373 citation statements)
references
References 37 publications
22
318
2
8
Order By: Relevance
“…This was unexpected as women are stereotyped as more emotional than men (Fabes and Martin (1991);Plant, Hyde, Keltner, and Devine (2000); Timmers, Fischer, and Manstead (2003)). Research appears to bear this out with females exceeding males in reported emotionality and emotion expressivity (Allen and Haccoun (1976); Gross and John (1995)).…”
Section: Discussionmentioning
confidence: 98%
“…This was unexpected as women are stereotyped as more emotional than men (Fabes and Martin (1991);Plant, Hyde, Keltner, and Devine (2000); Timmers, Fischer, and Manstead (2003)). Research appears to bear this out with females exceeding males in reported emotionality and emotion expressivity (Allen and Haccoun (1976); Gross and John (1995)).…”
Section: Discussionmentioning
confidence: 98%
“…They perceive women to be warm and emotionally expressive. Plant, et al, (2000) found that awe, disgust, distress, embarrassment, fear, guilt, happiness, love, sadness, shame, shyness, surprise, and sympathy were considered to be -feminine emotions.‖ Only anger, contempt and pride were thought to be -masculine emotions.‖ A number of researchers, using self-report measures, have found gender differences in the intensity of emotional experience (Brody & Hall, 2000;Diener, Sandvik, & Pavot, 1991;Fujita, Diener, & Sandvik, 1991. ) When we examine the scientific evidence, however, it appears that many assumed gender differences exist more in fantasy than in fact (Unger & Siiter, 1974;Maccoby & Jacklin, 1974;Hyde, 2007.…”
Section: Perhaps Men Are Simply Generally Less Emotional Than Are Womenmentioning
confidence: 99%
“…) Women are stereotyped as the emotional sex (Brody & Hall, 2000;Broverman, et al, 1972;Plant, Hyde, Keltner, & Devine, 2000). This stereotype appears to exist in most cultures (Fischer & Manstead, 2000).…”
Section: Perhaps Men Are Simply Generally Less Emotional Than Are Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Elsa's struggles as an outsider make her appealing, her inability to control her emotions (especially fear and anger) reflects the risks of mixing power with female volatility. This flaw conforms to stereotypes of women as temperamental (Feder 2014;Plant et al 2000;Schneider and Bos 2014) and even brings to mind the rage of Stephen King's Carrie who is set off by overpowering surges of emotion (Foundas 2013), characteristics incompatible with ruling. While Elsa struggles with her cryokinetic competence, Anna must learn how to navigate relationships with men, and which men she can trust.…”
Section: Postfeminist Struggles With Power and Romancementioning
confidence: 99%